We, the wolves: entre animais ferozes e irmandades do mal - Wittmann, Leonardo Josef Schifino (2020)
“We, the wolves: among ferocious animals and evil brotherhoods” is a thesis divided in two different parts. The first one, a screenplay written in English, tells the story of Kathryn, who searches for her missing sister in a vast and mysterious forest. It doesn’t take long, however, for our heroine to be the target of her sister’s kidnappers: an evil brotherhood of black-clothed men leaded by the maleficent Kraus. In this faery scenery, where evil seems to prevail, Kathryn will receive the help from Glen, a woodsman and long-time inhabitant of the woods, and from the best company she could have: the wolves leaded by the brave and ferocious Kincaid. Together, they will try to take down Kraus’s empire and reestablish the harmony of the forest. The second part of the thesis explores the fictional and theoretical influences that helped to build the story. First, a discussion is developed regarding the possibility of applying a literary style in a screenplay, using authors such as Walter Hill, Justin Marks, Angela Carter and Stephen King. Later on, some tools of the horror genre present in “We, the wolves” are analyzed, using the theory of North-American author Noël Carroll as the core for this study. For last, fairy-tale elements present in the screenplay are discussed, mainly through the perspective of the feminine figure of Kathryn; the ideas of Marie-Louise Von Franz and from the already mentioned Angela Carter serve as pillars for such a task.